2017
DOI: 10.1108/rmj-02-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Embedding a records manager as a strategy for helping to positively influence an organization’s records management culture

Abstract: Purpose This paper aims to explore the benefits of embedding a records manager into a team of university administrators to help them address their information management needs. Design/methodology/approach The paper describes an experience that was inspired by reports of successful experiences with embedded librarianship. The literature on records management culture and embedded librarianship is reviewed to identify best practices and criteria for success. These criteria are used to design and implement a pil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…In sum, it has been suggested that social integration, trust, and information exchange are closely related to each other (Hall and Widén-Wulff, 2008). This means that trust, plausibly both horizontal among employees (Bowker and Villamizar, 2017) and vertical towards management (Allen and Wilson, 2003), plays an integral role in the change-information sharing relationship.…”
Section: Trust As a Mediatormentioning
confidence: 99%
“…In sum, it has been suggested that social integration, trust, and information exchange are closely related to each other (Hall and Widén-Wulff, 2008). This means that trust, plausibly both horizontal among employees (Bowker and Villamizar, 2017) and vertical towards management (Allen and Wilson, 2003), plays an integral role in the change-information sharing relationship.…”
Section: Trust As a Mediatormentioning
confidence: 99%
“…Becoming embedded in the curriculum execution process requires a strong, continuous working relationship between the librarian, other support teams and academic teams, which involves sharing the responsibility of curriculum outcomes, inclusive of the development of workplace literacy skills (Bowker & Villamizar 2017). Ultimately, the goal of higher education is to educate students through the development of their intellectual abilities and to address development needs of society by providing knowledgeable and digitally skilled individuals who can contribute to the labour market.…”
Section: The Need For Embedded Library and Information Support Withinmentioning
confidence: 99%
“…Librarians bring research evidence and information skills right into the workplace, as well as helping teams to capture and share their know-how (HEE, 2017b). Team-based roles open up fresh opportunities to add value for instance managing data and advising on records management (Bowker & Villamizar, 2017) and through care navigation (Nix, Huber, Shapiro, & Pfeifle, 2016).…”
Section: Providing Business Critical Informationmentioning
confidence: 99%